Ecology and paleoenvironmental application of testate amoebae in peatlands of the high-elevation Colombian páramo. Issue 1 (18th February 2019) - Liu, Bing; Booth, Robert K.; Escobar, Jaime; Wei, Zhiqiang; Bird, Broxton W.; Pardo, Andres; Curtis, Jason H.; Ouyang, Jun
Abstract: We investigated the ecology and paleoecology of testate amoebae in peatlands of the Colombian páramo to assess the use of testate amoebae as paleoenvironmental indicators. Objectives were to (1) identify environmental controls on testate amoebae, (2) develop transfer functions for paleoenvironmental inference, and (3) examine testate amoebae in a Holocene peat core and compare our findings with other proxy records. Results from 96 modern samples indicate that testate amoebae are sensitive to pH and surface moisture, and cross-validation of transfer functions indicates potential for paleoenvironmental applications. Testate amoebae from the Triunfo Peatland in the Central Cordillera provided a proxy record of pH and water-table depth for the late Holocene, and inferred changes were correlated with peat C/N measurements during most of the record. Comparison with a lake-level reconstruction suggests that at least the major testate amoeba–inferred changes were driven by climate. Our work indicates that testate amoebae are useful paleoenvironmental indicators in high-elevation tropical peatlands.